Pengaruh Instrumen Kebijakan Makroprudensial Terhadap Risiko Sistemik Di Indonesia - I Made Hegar Danendra Nararya; Tony Seno Aji (Jurnal Ekonomika : INDEPENDEN, 2024)
The 2008/2009 crisis events that had a domino effect throughout the world had a devastating impact on the global economy, including Indonesia. This crisis highlighted the importance of establishing policies that are able to mitigate systemic risk. Macroprudential policies are increasingly encouraged by policy makers, especially by Bank Indonesia. With changes in the policy ratio limits set by Bank Indonesia from year to year, this study will further examine the effect of macroprudential policy instruments on banking systemic risk in Indonesia for the 2019-2023 period. This study will use a quantitative approach with a sample of KBMI IV and KBMI III banks. With the model used, namely the Fixed Effect Model, the results show that the LTV and RIM variables negatively affect systemic risk, but the PLM variable positively affects systemic risk.